PENGARUH NPL, CAR, DAN LDR TERHADAP ROA DI BANK BUKU 4 INDONESIA - Saeful Fachri; Anis F. Salam; Nia Safitri (Yudishtira Journal : Indonesian Journal of Finance and Strategy Inside, 2022)
This study was conducted to determine whether the Non Performing Loan, Capital Adequacy Ratio and Loan To Deposit Ratio have an effect on Return On Assets. The type of method used is the associative method, the population in this study is 35. Associative research is a study that aims to determine the relationship between two or more variables, so there are independent variables (variables that affect) and dependent (influenced). This study consists of independent variables, namely Non-Perfoarming Loan (X1), Loan to Deposit Ratio (X2) and Capital Adequacy Ratio (X3) and the dependent variable in this study is Return On Asset (Y). The results of the associative analysis show that the Non-Performing Loan, Capital Adequacy Ratio and Loan To Deposit Ratio are good, the results of multiple linear regression show that the regression coefficient value of the NPL variable is -0.557, the regression coefficient value of the CAR variable is 0.116 and the regression coefficient value of the LDR variable is 0.008. While the coefficient of determination (R2) is 0.466, it can be concluded that the magnitude of the effect of NPL, CAR and LDR on ROA is 46.6%. As well as hypothesis testing based on the results of the t-test for the NPL variable, the value of tcount < ttable (-2,015 < 1,693), for the CAR variable, the value of tcount > ttable (3.147 > 1.693) and for the LDR variable, the value of tcount < ttable (0.008 > 1.693) ). And based on the results of the F-test, the value of Fcount > Ftable (9.024 > 2.90). The conclusion of this study shows that NPL, CAR and LDR either partially or simultaneously are not significant and significant to ROA